(untitled) (Bioagro, 2022)
Tomato Brown Rugose Fruit Virus (ToBRFV) is transmitted mainly by contaminated seed or plant-to-plant infection during the crop; however, local climatic conditions can enhance the incidence and severity of the virus. The objective of this research was to determine the environmental suitability of the ToBRFV in Guanajuato State, Mexico. Vegetative material was collected with characteristic symptoms of ToBRFV to extract RNA by RT-PCR to amplify a segment of ORF2 of the genome of this virus. A database was created with the geographic location of the positive cases; then the maximum entropy algorithm was applied with 22 bioclimatic variables as predictors. On a surface of 288,104 ha located in Guanajuato (equivalent to 9.4 % of the State’s surface area), there are climatic conditions conducive to the incidence and severity of ToBRFV. The climatic variables that favor this incidence are: precipitation of the warmest four-month period (27.7 %), humidity regime (26.4 %) and average minimum temperature of the coldest year (17.0 %).